ANALISA KETINGGIAN PERMUKAAN AIR LAUT BERBASIS TEKANAN ATMOSFER UNTUK SISTEM PERINGATAN DINI TSUNAMI - Ledy Manuhutu; Yono Hadi Pramono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Have analyzed sea-level atmospheric pressure using a barometer-based altitude. From the measurement results obtained that any change in the height of one meter will change the pressure 0f 0,166 millibars. It can then be applied in the tools tsunami early warning system that has been in design ("YONOHAPE"). "YONOHAPE" is a buoy system above sea level that is equipped with an optical communication device or WIFI to the mainland. This detector can measure the amplitude of tsunami waves reached the height of 150 meters. Keyword - barometer altitude, atmospheric pressure, tsunami.